Challenges in teaching English writing skills: Lessons learnt from Indonesian high school English language teachers - Nurhardiyanti Adam; Abid Abid; Yusna Bantulu (Univeristas Negeri Gorontalo, 2021)
Writing skill, among the four target language skills, is one of the skills that language learners need to master. In teaching this skill, therefore, teachers should take any effort to help learners write using the language they learn correctly. However, in the context of teaching English in Indonesia, particularly the writing skill, teachers often face challenges. The study reported in this article seeks to identify the challenges experienced by several Indonesian English language teachers in teaching English writing skills at VHS, a vocational high school, in Gorontalo, Indonesia. The participants involved were all English language teachers working at the school. Data were collected using interview and observation, and analyzed by using a thematic analysis method. The findings showed that there were four themes describing the teachers’ challenges in teaching English writing skills. They were teaching technique-related challenges, teaching time-related challenges, linguistics-related challenges, and learning motivation-related challenges. Even though the teachers are able to cope with the challenges, they still need to explore more strategies in teaching, thus the teaching and learning process can run effectively.